Pengembangan Sistem Pelayanan Mobile Perpustakaan Universitas dengan Memanfaatkan Teknologi QR-Code (Studi Kasus: Universitas Islam Raden Rahmat) - Muhammad Ghalib Nugroho; Adam Hendra Brata; Mahardeka Tri Ananta (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
The Raden Rahmat Islamic University Library is a library that provides circulation divided into 3 services, the first is membership services, second loan services, and third loan status update services. Each service process is carried out on one officer and inadequate facilities. Some of them are the absence of a list of catalogs, the use of membership cards with poor quality, and the piled-up use of social media as a loan status update service. At the same time, one officer has to handle three services simultaneously, which hampers the circulation process. Therefore this research was conducted to build an application that can help or improve library circulation services for officers and members. Application development in this study uses the waterfall lifecycle with an object-oriented approach. Applications are developed using kotlin and jetpack compose programming languages. This application also supports scanning QR-Code to improve individual lending services and attendance instead of a guest book. The application has been tested on the unit, validation, and compatibility tests.